Estimation of genetic parameters for quantitative traits in pansy (Viola × wittrockiana) - KAUR, RAVNEET; DHATT, K K (The Indian Journal of Agricultural Sciences, 2020)
Genetic parameters of variability, heritability and genetic advance were evaluated to ascertain for various vegetative and floral characters in 36 genotypes (eight parents and its 28 F1's) of pansy. The highest coefficient of variation was observed in pod setting (8.82%) and lowest for flowering duration (2.08%). PCV was higher in magnitude with narrow differences than the GCV for all the characters studied. High PCV and GCV were observed for flower number followed by branch count, days from bud initiation to flowering, days to flowering and final plant height. High estimates of heritability were acquired for all traits. The traits flower number, branch count and days from bud initiation to flowering manifested high heritability (>80%) along with high genetic advance as % mean (>60%) indicating additive gene action in expression of these traits. So, further improvement in these traits could be brought by rehearse phenotypic selection.